Respuesta :
Answer:
[tex]f(x) = 3\, x + 6[/tex].
[tex]\displaystyle f(x) = 6\, \left(\frac{3}{2}\right)^{x}[/tex].
Step-by-step explanation:
A linear function in a cartesian plane can be written in the form:
[tex]f(x) = m\, x + k[/tex],
Where [tex]m[/tex] (slope) and [tex]k[/tex] ([tex]y[/tex]-intercept) are constants.
Given the two points [tex](0,\, 6)[/tex] and [tex](1,\, 9)[/tex], obtain two equations of [tex]m[/tex] and [tex]k[/tex] by substituting in the value of [tex](x,\, f(x))[/tex] at each point:
- [tex](0,\, 6)[/tex]: [tex]f(x) = 6[/tex] when [tex]x = 0[/tex]. Hence, [tex]6 = (m)\, (0) + k[/tex], which simplifies to [tex]k = 6[/tex].
- [tex](1,\, 9)[/tex]: [tex]f(x) = 9[/tex] when [tex]x = 1[/tex]. [tex]9 = (m)\, (1) + k[/tex]. Substitute in [tex]k = 6[/tex] to obtain [tex]m = 3[/tex].
Hence, the equation of this linear function would be:
[tex]f(x) = 3\, x + 6[/tex].
An exponential function in a cartesian plane can be written in the form:
[tex]f(x) = a\, b^{x}[/tex],
Where [tex]a \ne 0[/tex] and [tex]b > 0[/tex] are constants.
Similar to the example of the linear equation, the two points [tex](0,\, 6)[/tex] and [tex](1,\, 9)[/tex] provide two equations for [tex]a[/tex] and [tex]b[/tex]:
- [tex](0,\, 6)[/tex]: [tex]6 = a\, b^{0}[/tex]. Since [tex]b > 0[/tex], [tex]b^{0} = 1[/tex]. Hence, this equation simplifies to [tex]a = 6[/tex].
- [tex](1,\, 9)[/tex]: [tex]9 = a\, b^{1}[/tex]. Substitute in [tex]k = 6[/tex] to obtain [tex]b = (3/2)[/tex].
Hence, the equation of this exponential function would be:
[tex]\displaystyle f(x) = 6\, \left(\frac{3}{2}\right)^{x}[/tex].